2016
DOI: 10.1038/ijir.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sexual functions and marital adjustment of pregnant women in Turkey

Abstract: The aim of this study was to evaluate pregnant women's sexual function and marital adjustment. The sample of the study included 298 women, and it was evaluated using Golombok Rust Inventory of Sexual Satisfaction (GRISS) Scale and Marital Adjustment Scale. The most important reasons for decreasing the frequency of sexual intercourse included the fear of harming the fetus during intercourse (62.1%), fear of having miscarriage (47.8%) and decreased sexual desire (34.7%). It was found that women with sexual dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
3
21
3
5
Order By: Relevance
“…Bu tanımlamayla, çiftlerden her ikisinin de ilişki sürdürebilme kapasiteleri evlilik uyumunu sağlamak için önemli hale gelmektedir (5). Evlilik uyumu ile ilgili yapılan araştırmalardan, cinsiyet, çocuk sahibi olma durumu, evlilik biçimi, evlilik süresi, yaş, evlilik yaşı, tanışma süresi gibi faktörlerin evlilik uyumunu etkilediği görülmüştür (6)(7)(8).…”
unclassified
“…Bu tanımlamayla, çiftlerden her ikisinin de ilişki sürdürebilme kapasiteleri evlilik uyumunu sağlamak için önemli hale gelmektedir (5). Evlilik uyumu ile ilgili yapılan araştırmalardan, cinsiyet, çocuk sahibi olma durumu, evlilik biçimi, evlilik süresi, yaş, evlilik yaşı, tanışma süresi gibi faktörlerin evlilik uyumunu etkilediği görülmüştür (6)(7)(8).…”
unclassified
“…In this study, it was found that the prevalence of sexual dysfunction was higher in women with a perception of inadequate income, chronic disease, and vaginal discharge. In the studies of Yanıkkerem et al (17), it was found that low-income level increased the risk of sexual dysfunction. The insufficiency of income makes the living conditions of people difficult and increases the level of stress, and this is thought to negatively affect sexual desire and sexual function in women (17).…”
Section: Discussionmentioning
confidence: 97%
“…In the studies of Yanıkkerem et al (17), it was found that low-income level increased the risk of sexual dysfunction. The insufficiency of income makes the living conditions of people difficult and increases the level of stress, and this is thought to negatively affect sexual desire and sexual function in women (17). Also, Zsoldos et al (18) showed in their studies that the presence of chronic disease negatively affects sexual function.…”
Section: Discussionmentioning
confidence: 97%
“…Štatisticky významné rozdiely sa preukázali medzi prvým a tretím trimestrom ako aj medzi druhým a tretím trimestrom. Viacero štúdií potvrdilo zníženie sexuálnej túžby, iniciatívy, aktivity žien, zníženie koitálnej frekvencie počas celého tehotenstva, zvlášť v treťom trimestri tehotenstva ako aj zníženú schopnosť prežívať orgazmus a súlad s partnerom [3,7,[23][24][25][26][27]. Ahmed et al [19] štúdiou zistili, že sexuálna aktivita klesá počas tehotenstva, avšak bol zaznamenaný aj mierny nárast počas druhého trimestra.…”
Section: Diskusiaunclassified
“…Najčastejšími dôvodmi zníženej sexuálnej aktivity u žien zapojených do štúdie bol strach, únava, nepohodlie a nevoľnosť. Podobne v štúdii Yanikkerem et al [27] sa ako najdôležitejšie dôvody zníženia frekvencie pohlavného styku preukázali strach z poškodenia plodu počas pohlavného styku (62,1 %), strach z potratu (47,8 %) a rovnako aj zníženie sexuálnej túžby (34,7 %). Efe et al [14] uvádzajú obdobné dôvody zníženej sexuálnej aktivity počas tehotenstva, a to letargiu, strach o plod, nevoľnosť, vracanie, únavu, dyspareuniu a pod.…”
Section: Diskusiaunclassified